Selection of electrodes for the ˝in situ˝ electrical resistivity measurements of molten aluminium - Petrič, Mitja; Kastelic, Sebastjan; Mrvar, Primož (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The aim of this paper is the selections of proper electrode material for four-probe technique electrical resistivity measurement of aluminium and aluminium alloys. The biggest problem of electrodes is oxidation during measurement causing high contact resistance and giving wrong results. Various materials have been tested and aluminium electrodes have been chosen. Advantage of aluminium electrodes is that they are melted in specimen right after the pouring and causing no interface which is resulting with any contact resistance. The device together with measuring cell for ˝in situ˝ measurement of electrical resistivity was developed using four-probe DC technique.